2021
DOI: 10.3389/fpubh.2020.574505
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Teleneurology in Sub-Saharan Africa: Leveraging the Current Exigency

Abstract: Africa has over 1.3 billion inhabitants, with over 60% of this population residing in rural areas that have poor access to medical experts. Despite having a ridiculously huge, underserved population, very few African countries currently have any form of sustained and organized telemedicine practice, and even fewer have dedicated tele-neurology services. The ongoing COVID-19 pandemic has proved to be one of the most significant disruptors of vital sectors of human endeavor in modern times. In the healthcare sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…However, to operationalize this, PWNDs and their caregivers must be thoroughly educated about these aspects of TNR. The literacy and understanding about tele-rehabilitation and use of tele-communication technologies for rehabilitation has been poor among those PWNDs even before the pandemic in many LMICs especially in Sub-Saharan Africa ( 29 , 30 ). Considering these aspects will be crucial to enhance TNR services and enable service providers to achieve neurorehabilitation goals in a realistic way within their environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, to operationalize this, PWNDs and their caregivers must be thoroughly educated about these aspects of TNR. The literacy and understanding about tele-rehabilitation and use of tele-communication technologies for rehabilitation has been poor among those PWNDs even before the pandemic in many LMICs especially in Sub-Saharan Africa ( 29 , 30 ). Considering these aspects will be crucial to enhance TNR services and enable service providers to achieve neurorehabilitation goals in a realistic way within their environment.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported a major lack of studies on telemedicine progress to serve as a baseline for indicating users' satisfaction with telemedicine services. Adebayo, et al [11] limited their study to teleneurology practice and infrastructural preparedness in SSA, which limits the extent to which various countries in SSA have made progress in terms of telemedicine implementation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ongoing pandemic has created impediments in healthcare delivery, including imaging services. Healthcare services, health education, and health information have seen a shift to remote delivery through telehealth ( 2 ). All noninvasive imaging such as digitized x - rays, computed tomography (CT) scan, magnetic resonance imaging (MRI), and ultrasound scan can be interpreted through teleradiology.…”
mentioning
confidence: 99%
“…Inaccurate interpretation of radiological images leads to higher morbidity and mortality in Africa ( 6 ). Sub-Saharan Africa (SSA) has an enormous health care burden, but is the region with the lowest level of economic, technological, and internet development ( 2 ). Telemedicine in Africa is limited by basic infrastructures such as steady electrical power, cellular network coverage, and slow internet connectivity ( 7 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation